CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

Moxibustion pre-treatment attenuates seizure severity during status epilepticus and counteracts the proconvulsant function of the purinergic P2X7 receptor - Hong-Wei Zhang; Jia-Jia Li; Yulihan Tang; Mao-Lin Tian; Sheng Huang; Meng-Juan Sun (Purinergic Signalling, 2025)

Astrocytic P2X7 receptor in retrosplenial cortex drives electroacupuncture analgesia - Wei Zhao; Si-Le Liu; Si-Si Lin; Ying Zhang; Chang Yu (Purinergic Signalling, 2025)

Role and recent progress of P2Y12 receptor in cancer development - Yanni Xi; Zhenya Min; Mianxue Liu; Xueqin Lin; Zhao-hua Yuan (Purinergic Signalling, 2025)

Functional role of P2X7 purinergic receptor in cancer and cancer-related pain - Yong-sheng Xu; Jun Xiang; Si-jian Lin (Purinergic Signalling, 2025)

P2 purinergic receptors regulate the progression of colorectal cancer - Wen-jun Zhang; Li-peng Zhang; Si-jian Lin; Cheng-yi Wang; Yi-guan Le (Purinergic Signalling, 2025)

Correction to: Role and recent progress of P2Y12 receptor in cancer development - Yanni Xi; Zhenya Min; Mianxue Liu; Xueqin Lin; Zhao-hua Yuan (Purinergic Signalling, 2024)

Correction to: P2 purinergic receptors regulate the progression of colorectal cancer - Wen‑jun Zhang; Li‑peng Zhang; Si‑jian Lin; Cheng‑yi Wang; Yi-guan Le (Purinergic Signalling, 2024)

Potential role of the P2X7 receptor in the proliferation of human diffused large B-cell lymphoma - Xiao Yang; Yuanyuan Ji; Lin Mei; Wenwen Jing; Xin Yang; Qianwei Liu (Purinergic Signalling, 2024)

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

Adenosine A2A receptor controls the gateway of the choroid plexus - Mengqian Ye; Mengru Wang; Yijia Feng; Huiping Shang; Yuwen Yang; Lanxin Hu; Muran Wang; Serhii Vakal; Xiangxiang Lin; Jiangfan Chen; Wu Zheng (Purinergic Signalling, 2023)

P2X7Rs: new therapeutic targets for osteoporosis - Haoyun Huang; Yu-Mei He; Miao-Miao Lin; Yanchao Wang; Xiaomei Zhang; Li Liang; Xueling He (Purinergic Signalling, 2023)
Increasing evidence suggests that both the occurrence and progression of osteoporosis are associated with inflammation, especially in primary osteoporosis. The maintenance of skeletal homeostasis is dependent on the complex regulation of bone metabolism. Numerous evidence suggested that purinoceptor networks are essential for bone homeostasis. In this review, the relationship between inflammation and the development of osteoporosis and the role of P2X7 receptor (P2X7R) in regulating the dynamic regulation of bone reconstruction were covered. We also discussed how P2X7R regulates the balance between resorption and bone formation by osteoblasts and reviewed the relevance of P2X7R polymorphisms in skeletal physiology. Finally, we analyzed potential targets of P2X7R for osteoporosis.

Purinergic signaling: a potential therapeutic target for depression and chronic pain - Yuting Zou; Runan Yang; Lin Li; Xiumei Xu; Shangdong Liang (Purinergic Signalling, 2023)

Structural basis for the functional properties of the P2X7 receptor for extracellular ATP - Lin-Hua Jiang; Emily A. Caseley; Steve P. Muench; Sébastien Roger (Purinergic Signalling, 2021)
The P2X7 receptor, originally known as the P2Z receptor due to its distinctive functional properties, has a structure characteristic of the ATP-gated ion channel P2X receptor family. The P2X7 receptor is an important mediator of ATP-induced purinergic signalling and is involved the pathogenesis of numerous conditions as well as in the regulation of diverse physiological functions. Functional characterisations, in conjunction with site-directed mutagenesis, molecular modelling, and, recently, structural determination, have provided significant insights into the structure–function relationships of the P2X7 receptor. This review discusses the current understanding of the structural basis for the functional properties of the P2X7 receptor.

Contribution of Val/Ile87 residue in the extracellular domain in agonist-induced current responses of the human and rat P2X7 receptors - Emily A Caseley; Stephen P Muench; Lin-Hua Jiang (Purinergic Signalling, 2020)
The P2X7 receptor (P2X7R) is an ATP-gated cation channel with a critical role in many physiological and pathological processes, and shows prominent functional differences across mammalian species, exemplified by larger current responses of the rat (r) P2X7R to ATP and its analogue BzATP and a greater sensitivity to agonists compared with the human (h) P2X7R. Here, we showed that substitution of Val87 residue in the extracellular domain of the hP2X7R with isoleucine in the rP2X7R increased the current responses of the hP2X7R to both ATP and BzATP. Conversely, introduction of reciprocal I87V mutation in the rP2X7R led to a noticeable but statistically insignificant reduction in the current responses of the rP2X7R to ATP and BzATP. The mutations did not affect the sensitivity of the human and rat P2X7Rs to ATP and BzATP. These results suggest a contribution of Val/Ile87 in agonist-induced current responses of human and rat P2X7Rs, which helps to better understand the molecular determinants for species-dependent function of the mammalian P2X7Rs.

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Inhibition of the adenosinergic pathway: the indispensable part of oncological therapy in the future - Yi Huang; Zili Gu; Yang Fan; Guangxi Zhai; Xiaogang Zhao; Qifeng Sun; Yanbin Shi; Guimei Lin (Purinergic Signalling, 2019)

POM-1 inhibits P2 receptors and exhibits anti-inflammatory effects in macrophages - Gabriela Pimenta-dos-Reis; Eduardo José Lopes Torres; Paula Gabriela Quintana; Lincon Onorio Vidal; Bárbara Andréa Fortes dos Santos; Chuan-Sheng Lin; Norton Heise; Pedro Muanis Persechini; Julieta Schachter (Purinergic Signalling, 2017)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Conformational changes during human P2X7 receptor activation examined by structural modelling and cysteine-based cross-linking studies - Emily A Caseley; Stephen P Muench; Lin-Hua Jiang (Purinergic Signalling, 2017)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

Enhancement of purinergic signalling by excessive endogenous ATP in resiniferatoxin (RTX) neuropathy - Chih-Lung Lin; Yaw-Syan Fu; Tin-Hsin Hsiao; Yu-Lin Hsieh (Purinergic Signalling, 2013)

Differential expression of P2Y receptors in the rat cochlea during development - Lin-Chien Huang; Peter R. Thorne; Srdjan M. Vlajkovic; Gary D. Housley (Purinergic Signalling, 2010)

Loss of apical monocilia on collecting duct principal cells impairs ATP secretion across the apical cell surface and ATP-dependent and flow-induced calcium signals - Michael B. Hovater; Dragos Olteanu; Elizabeth L. Hanson; Nai-Lin Cheng; Brian Siroky; Attila Fintha; Peter Komlosi; Wen Liu; Lisa M. Satlin; P. Darwin Bell; Bradley K. Yoder; Erik M. Schwiebert (Purinergic Signalling, 2008)

Extracellular zinc and ATP-gated P2X receptor calcium entry channels: New zinc receptors as physiological sensors and therapeutic targets - Erik M. Schwiebert; Lihua Liang; Nai-Lin Cheng; Clintoria Richards Williams; Dragos Olteanu; Elisabeth A. Welty; Akos Zsembery (Purinergic Signalling, 2005)